2017
DOI: 10.1063/1.4999090
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations on ductile-brittle transition in ⟨111⟩ BCC Fe nanowires

Abstract: Molecular dynamics simulations have been performed to understand the influence of temperature on the tensile deformation and fracture behavior of <111> BCC Fe nanowires. The simulations have been carried out at different temperatures in the range 10-1000 K employing a constant strain rate of 1× 10 8 s −1 . The results indicate that at low temperatures (10-375 K), the nanowires yield through the nucleation of a sharp crack and fails in brittle manner. On the other hand, nucleation of multiple 1/2<111> dislocati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…16 Sainath et al studied the influence of temperature, ranging from 10 to 1000 K, on the tensile deformation and fracture behavior of h111i BCC Fe NWs using MD simulation under a constant strain rate of 1 Â 10 8 s À1 . 14 Similarly, they also observed that the subsequent deformation of all the NWs exhibits non-linear deformation behaviour after the initial linear elastic regime until the onset of the plastic deformation regime at relatively high strains 4B0.04, which is in close agreement with our linear yield strain values. Notably, non-linear deformation highly depends on the temperature of the system.…”
Section: Tensile Mechanical Properties Of Fe Nws and Oxidized Fe Nwssupporting
confidence: 86%
See 3 more Smart Citations
“…16 Sainath et al studied the influence of temperature, ranging from 10 to 1000 K, on the tensile deformation and fracture behavior of h111i BCC Fe NWs using MD simulation under a constant strain rate of 1 Â 10 8 s À1 . 14 Similarly, they also observed that the subsequent deformation of all the NWs exhibits non-linear deformation behaviour after the initial linear elastic regime until the onset of the plastic deformation regime at relatively high strains 4B0.04, which is in close agreement with our linear yield strain values. Notably, non-linear deformation highly depends on the temperature of the system.…”
Section: Tensile Mechanical Properties Of Fe Nws and Oxidized Fe Nwssupporting
confidence: 86%
“…Once plastic deformation is begun for all NWs, the nucleation and growth of twinning occurs at a relatively smaller stress value, but it fluctuates almost at a constant value of the flow stress, as seen from the stress-strain curves. 14,17,55 The work of hardening rate of all the Fe NWs is obtained by integration of the area under the tensile stress-strain curves. 33 The oxide shell layer including local structure has an effect on the work of hardening rate as is observed from the tensile stress-strain curves.…”
Section: Tensile Mechanical Properties Of Fe Nws and Oxidized Fe Nwsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Therefore, the constitutive parameters in this paper are obtained from stress-strain behavior based on nanowire stretching. 21,22 Then the mechanical behaviors of the substrate are investigated in detail, which include the indentation load-displacement curves, pressures, adhesive regions as well as the stress distributions. Because molecular dynamics (MD) can be used to predict particles trajectory by interatomic potentials or MD force fields [23][24][25][26] in the adhesive contact, in the end, the proposed method is compared with MD simulation.…”
Section: Introductionmentioning
confidence: 99%